METODE MODELLING THE WAY UNTUK MENINGKATKAN HASIL BELAJAR SAINS SISWA KELAS III SD - Bayu Aditama, Wiranda; Mukarromah, Aenullael (JURNAL KAJIAN ISLAM MODERN, 2024)
This research aims to improve the science learning outcomes of third grade elementary school students through the application of the modeling the way method.The subjects of this research were 26 grade III elementary school students consisting of 16 male students and 10 female students. The method in this research is classroom action research which is carried out in two cycles where each cycle consists of several stages, including planning, implementation, observation and reflection. Data on student learning outcomes is obtained from written tests at the end of each cycle, while teacher and student activities are obtained from observation instruments. Indicators of success in learning outcomes are said to have increased if ≥ 85% of students get a score of ≥ 65, while indicators of success in teacher activities are at least in the good category and indicators of student activity are at least in the "active" category. Based on the research results, data obtained on improving the quality of the learning implementation process, namely for teaching activities in cycle I, teachers obtained a score of 34 in the quite good category and in cycle II it increased by obtaining a score of 41 in the good category. Likewise for student learning activities in cycle I obtained a score of 33 in the quite active category and in cycle II it increased by obtaining a score of 40 in the good category. For student learning outcomes, the average score in cycle I was 70.3 with a classical completeness percentage of 69.2% and there was an increase in the second cycle with an average score of 85.4 with a classical completeness percentage of 85.1%, the conclusion of This research is that the application of the way modeling method can improve students' science learning outcomes in class III elementary school.